2009
DOI: 10.1038/sc.2009.89
|View full text |Cite
|
Sign up to set email alerts
|

Responses of microRNAs 124a and 223 following spinal cord injury in mice

Abstract: Study design: We investigated microRNA (miRNA) expression after spinal cord injury (SCI) in mice. Objectives: The recent discovery of miRNAs suggests a novel regulatory control over gene expression during plant and animal development. MiRNAs are short noncoding RNAs that suppress the translation of target genes by binding to their mRNAs, and play a central role in gene regulation in health and disease. The purpose of this study was to examine miRNA expression after SCI. Setting: Department of Orthopaedic Surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 19 publications
4
60
3
Order By: Relevance
“…Therefore, miR-199a-3p may limit spinal cord injury resulting from hypoxia and may control inflammation and ERK-MAPK signaling, which has been shown to participate in injury after IRI. Of particular note is miRNA-124a and miRNA-233, which are differentially expressed after spinal cord injury reported by Nakanishi et al (2), showed no significant change in our study. It may be due to the difference in mouse model between our study and that in the article of Nakanishi et al…”
Section: Short Communicationcontrasting
confidence: 65%
See 1 more Smart Citation
“…Therefore, miR-199a-3p may limit spinal cord injury resulting from hypoxia and may control inflammation and ERK-MAPK signaling, which has been shown to participate in injury after IRI. Of particular note is miRNA-124a and miRNA-233, which are differentially expressed after spinal cord injury reported by Nakanishi et al (2), showed no significant change in our study. It may be due to the difference in mouse model between our study and that in the article of Nakanishi et al…”
Section: Short Communicationcontrasting
confidence: 65%
“…A number of microRNAs were found in the mammalian brain and spinal cord, where they are involved in the regulation of several nervous diseases (1). Recently, several reports have revealed important roles of microRNAs in traumatic SCI (2,3). We here describe for the first time microRNA expression profiling of ischemic rat spinal cord in the context of pre-treatment with atorvastatin using a quantitative real-time PCR based array.…”
Section: Short Communicationmentioning
confidence: 99%
“…Our previous study also reported a marked change of expression levels of mir-124a and mir-223 in spinal cord tissue of mice following SCI. 17 However, the expression levels of serum miRNAs were not reported in these previous reports. Additionally, the expression levels of these miRNAs in the serum were not specifically associated with the severity of SCI in miRNA microarray assay in the present study.…”
Section: Micrornas As Biomarkers Of Spinal Cord Injurymentioning
confidence: 81%
“…The novel finding is that all members of the Let-7 family of miRNAs studied were increased as much as 3-fold in a time course parallel to the emergence of pain-related behaviors developed after SCI. While several studies have analyzed miRNA expression and functional changes with SCI, many are microarray studies providing conflicting information regarding overall patterns of these changes [25][26][27]. It has been suggested that many of these discrepancies may be attributable to model and severity of injury or even statistical analyses employed [19].…”
Section: Discussionmentioning
confidence: 99%